2022
DOI: 10.1099/jgv.0.001758
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the heterogeneity of natural viruses in mouse studies

Abstract: Animal models are a critical tool in modern biology. To increase reproducibility and to reduce confounding variables modern animal models exclude many microbes, including key natural commensals and pathogens. Here we discuss recent strategies to incorporate a natural microbiota to laboratory mouse models and the impacts the microbiota has on immune responses, with a focus on viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…All methods were in agreements regarding their size distribution—centered between 25Kbp and 75Kbp (Figure 6C). This is in accordance with known sizes of DNA viruses infecting Bacteria and Archaea that are likely the most abundant hosts in the gut microbiome obtained from fecal samples (5355). This suggests that if viruses are the targeted diversity for a study, the addition of long-reads may not substantially improve results.…”
Section: Resultssupporting
confidence: 86%
“…All methods were in agreements regarding their size distribution—centered between 25Kbp and 75Kbp (Figure 6C). This is in accordance with known sizes of DNA viruses infecting Bacteria and Archaea that are likely the most abundant hosts in the gut microbiome obtained from fecal samples (5355). This suggests that if viruses are the targeted diversity for a study, the addition of long-reads may not substantially improve results.…”
Section: Resultssupporting
confidence: 86%
“…This model thus permits specific dissection of the microbial factors and host pathways that contribute to these immune phenotypes. While the variable exposures achieved via cohousing of SPF mice with wild or pet shop mice may better model the breadth of immune exposures experienced by humans (14), intentional exposures that appropriately mimic the "average" exposures experienced by humans in HICs or LMICs also could inform our understanding of the diversity of human immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cohousing of SPF mice with wild or pet shop-derived mice, rewilding by exposing SPF mice to a natural environment, and "wildling" models in which transferred lab mouse embryos are sired by wild mothers (6,(8)(9)(10)(11)(12), have provided critical comparisons between "exposed" and naïve SPF mice. These alternative "dirty" models reproduce natural microorganism exposures including bacteria, eukaryotic viruses, bacteriophages, fungi, helminths and/or mites (13,14), and exhibit fundamental shifts in their immune systems, improving their ability to recapitulate essential aspects of human immunity (5,6,9). Co-housing laboratory mice results in the replication of immune phenotypes and transcriptional signatures found in wild mice or humans, including altering T cell differentiation and modulating susceptibility to new pathogens (6).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that SPF mice do not recapitulate human immune responses to vaccination and that introducing microbial experiences yields vaccine responses that better recapitulate those observed in humans ( 6 , 7 ). There are several models that have been developed to reintroduce natural mouse and environmental pathogens to laboratory mice to better recapitulate the human immune system ( 10 ). However, no one model can capture the complexity of human exposures across space and time.…”
Section: Observationmentioning
confidence: 99%